Beloit, Wisconsin and the Great Migration - Knowles, Lucas W. (My University, 2010)
The Great Migration of southern Blacks to northern cities in the first half of the twentieth century is a well documented historical topic. Southern Blacks who had grown restive of the Jim Crow South headed north to urban settings seeking employment and a better life. As a result of this process, many Midwestern cities such as Chicago and Milwaukee experienced drastic social changes. Another city which became a destination during the Great Migration is the small city of Beloit, Wisconsin. Early twentieth century Beloit was a lively manufacturing locale centered on Wisconsin's southern border. At the onset of the First World War, Fairbanks, Morse and Company was experiencing a manpower shortage. To fill the void Fairbanks, Morse and Company began recruiting southern Black men to work in their factory. By offering jobs and housing, Fairbanks, Morse and Company established Beloit as a destination for southern Blacks seeking to leave the South.
Color poster with text and images.
Keywords: Beloit (Wis.)--History; African Americans--Wisconsin--Beloit--History; African Americans--Migration--History--20th century; Posters; Migration, Internal--United States--History--20th century